(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This study explores vocabulary enrichment and pronunciation correction in preschool children, focusing on the linguistic, cognitive, and social factors influencing early language development. It emphasizes the importance of rich language environments, interactive conversations, and phonological awareness activities for vocabulary growth and pronunciation.